Financing Risk Management in Islamic Banks - Binda Rahma Cahyani; Wahyu Febri Ramadhan Sudirman (General Multidisciplinary Research Journal, 2026)
Introduction:Financing risk management is a fundamental component of Islamic banking operations because it is directly linked to the potential emergence of non-performing financing (NPF), which may threaten financial stability and long-term performance. Islamic banks operate under Sharia principles that prohibit interest (riba) and emphasize profit-and-loss sharing contracts such as mudharabah and musyarakah. These unique characteristics create a distinct and relatively more complex risk profile compared to conventional banks. Financing risk arises not only from customers’ inability to fulfill contractual obligations but also from information asymmetry, moral hazard, weak monitoring systems, and fluctuating macroeconomic conditions. Methods:This study applies a qualitative approach using a systematic literature review. Relevant national and international journal articles published within the last ten years were collected and analyzed to examine financing risk management practices, determinants of financing risk, and their implications for Islamic banking stability. Results:The findings show that comprehensive risk management covering risk identification, measurement, monitoring, and control significantly reduces NPF levels and strengthens Islamic banks’ resilience during economic uncertainty. Internal factors such as corporate governance quality, effective internal control systems, and managerial competence substantially influence financing risk levels. External factors, including macroeconomic stability, regulatory policies, and overall financial system conditions, also contribute to financing risk dynamics. Conclusion and Suggestion: Strengthening financing risk management is essential to ensure sustainability, credibility, and long-term growth. Islamic banks should enhance governance practices, improve monitoring mechanisms, and continuously adapt risk mitigation strategies to evolving economic and regulatory environments.